IMPLEMENTASI GOOGLE DRIVE CLOUD STORAGE PADA SISTEM REPOSITORI AL-DARING - Ketut Agus Seputra; A.A. Gede Yudhi Paramartha; I Nyoman Saputra Wahyu Wijaya (Prahasta Publisher, 2022)
One of the steps of accreditation for institutions and study programs during the epidemic is online assessment (AL-Daring). The availability of suitable information and communication technologies to enable the AL-Daring process is one of the consequences of AL-Daring. Supporting data must be provided in the form of a soft copy in the University Information System that assessors may access appropriately. How the Information System can help Study Program Managers and Accreditation Applicants complete documentation more quickly and efficiently is also crucial. It's also important to note that each Study Program and Study Program Manager will upload a large number of papers of various types and sizes. As a result, various factors that affect the quality of information systems, such as data and storage space availability, ease of access, and timeliness, must be satisfied. The AL-Daring Information System is being developed using agile methodologies in the aim of completing it faster so that it can be utilized right away and adapt to user needs. To perform successfully, this system was built using the Codeigniter framework and Google Drive Cloud Storage as a document storage medium via the Google Drive API service. SUS rates the repository system an excellent score on an adjective rating claiming the system is very useful and well-received by users.